Long-term stability of acquired drug resistance and resistance associated mutations in the fungal pathogen Nakaseomyces glabratus (Candida glabrata) - Ksiezopolska, Ewa; Schikora-Tamarit, Miquel Àngel; Carlos Nunez-Rodriguez, Juan; Gabaldón, Toni (Frontiers in Cellular and Infection Microbiology, 2024)
The limited number of available antifungal drugs and the increasing number of fungal isolates that show drug or multidrug resistance pose a serious medical threat. Several yeast pathogens, such as Nakaseomyces glabratus (Candida glabrata), show a remarkable ability to develop drug resistance during treatment through the acquisition of genetic mutations. However, how stable this resistance and the underlying mutations are in non-selective conditions remains poorly characterized. The stability of acquired drug resistance has fundamental implications for our understanding of the appearance and spread of drug-resistant outbreaks and for defining efficient strategies to combat them. Here, we used an in vitro evolution approach to assess the stability under optimal growth conditions of resistance phenotypes and resistance-associated mutations that were previously acquired under exposure to antifungals. Our results reveal a remarkable stability of the resistant phenotype and the underlying mutations in a significant number of evolved populations, which conserved their phenotype for at least two months in the absence of drug-selective pressure. We observed a higher stability of anidulafungin resistance over fluconazole resistance, and of resistance-conferring point mutations as compared with aneuploidies. In addition, we detected accumulation of novel mutations in previously altered resistance-associated genes in non-selective conditions, which suggest a possible compensatory role. We conclude that acquired resistance, particularly to anidulafungin, is a long-lasting phenotype, which has important implications for the persistence and propagation of drug-resistant clinical outbreaks.